Hormonal regulation of ethylene response factors in tomato during storage and distribution - Park, Me-Hea; Yang, Hae-Jo; Malka, Siva Kumar (Frontiers in Plant Science, 2023)
Ethylene response factors (ERFs) play a critical role in regulating hormone interactions that affect the shelf life of tomatoes. Understanding their regulation during storage and distribution can be highly beneficial. This study examined the effects of treatment with ethylene (ET), brassinosteroid (BR), auxin (AUX), and gibberellin (GA) on fruit ripening and the expression of 18 ripening-associated ERFs in tomato stored at 20 °C (room temperature) for 10 d or 4 °C (cold storage) for 14 d followed by 2 d at 20 °C (retailer conditions). The results showed that ripening was accelerated by ET and BR but was delayed by AUX and GA at room temperature. Cold storage delayed ripening in all groups, with ET and GA treatments showing the highest and lowest a* values, respectively. The effects of hormone treatment were consistent with room temperature when the fruits were transferred from cold storage to retail conditions. At room temperature, ERFs responsive to ET (ERF.B1, B2, B6, E2, and F1) and BR (ERF.E5, F2, and F3) were inhibited by AUX. ET-induced genes (ERF.C1, E1, F4, and H7) could be co-regulated by other hormones at cold storage. When the fruits were transferred from cold storage to retailer conditions, ERFs responsive to ET and BR were inhibited by GA. Additionally, ET-responsive ERFs could be inhibited by BR at room temperature, whereas ET could inhibit BR-responsive ERFs at retailer conditions. The same ERFs that were regulated by ET at room temperature were instead regulated by BR under retailer conditions, and vice versa. These findings can help provide a better understanding of the complex hormone interactions regulating the postharvest physiology of tomato and in maintaining its quality and shelf life during storage and distribution.